2002
DOI: 10.1002/1521-3773(20020315)41:6<1053::aid-anie1053>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Click Chemistry In Situ: Acetylcholinesterase as a Reaction Vessel for the Selective Assembly of a Femtomolar Inhibitor from an Array of Building Blocks

Abstract: Form‐fitting chemistry in a protein mold is enabled by the use of the 1,3‐dipolar cycloaddition of azides and alkynes. The enzyme acetylcholinesterase preferentially assembles one pair of these reactants, each of which bears a group that binds to adjacent positions on the protein structure (see picture), into a 1,2,3‐triazole adduct that is the most potent noncovalent inhibitor of the enzyme yet developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
219
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 697 publications
(233 citation statements)
references
References 60 publications
3
219
0
3
Order By: Relevance
“…More importantly, the cycloaddition reaction can be conducted in aqueous solution in the absence of deleterious reagents, thus allowing direct screening and identification of hits from the library. In fact, click chemistry has found increasing applications in lead discovery and optimization for a number of enzymes including the PTPs (27)(28)(29)(30)(31). The azide-containing building blocks were synthesized in a one-pot procedure, in which alkyl or aryl amines were reacted with the acyl chloride linkers in N,N-Dimethylformamide (DMF), followed by S N 2 reaction with sodium azide to generate the corresponding azides.…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, the cycloaddition reaction can be conducted in aqueous solution in the absence of deleterious reagents, thus allowing direct screening and identification of hits from the library. In fact, click chemistry has found increasing applications in lead discovery and optimization for a number of enzymes including the PTPs (27)(28)(29)(30)(31). The azide-containing building blocks were synthesized in a one-pot procedure, in which alkyl or aryl amines were reacted with the acyl chloride linkers in N,N-Dimethylformamide (DMF), followed by S N 2 reaction with sodium azide to generate the corresponding azides.…”
Section: Resultsmentioning
confidence: 99%
“…The in situ click chemistry for drug discovery is dependent on irreversibly reacting reagents that are inert under physiological conditions, 27 as shown earlier by the discovery of highly potent inhibitors of acetylcholine esterase, [28][29][30][31] carbonic anhydrase II 32 and HIV-1 protease. 33 …”
Section: Introductionmentioning
confidence: 99%
“…The diversity of chemical structures of the 1,2,3-triazole family and their useful biological activities made these compounds attractive targets in synthetic organic chemistry and many studies have been reported on the synthesis of these compounds [7][8][9]. The title compound is isomorphous with the ethyl 1-(4-bromophenyl)-5-methyl-1H-1,2,3-triazole-4 carboxylate analogue, reported by Singh, et al [10].…”
Section: Discussionmentioning
confidence: 99%